Reglas de transformación para realizar migración completa de bases de datos relacionales SQL a bases de datos no relacionales de tipo documental (2017)
The present work proposes the transformation rules for migrate relational database to documental non-relational database. This proffer is based in the identification of similarities and differences between the two management systems database, therewith, identify integration points. From there is sets a process from migrate relational database, that includes disciplines, responsible, and in-out templates in order to apply fully the defined transformations. The process is supported in Eclipse Process Framework Composer SPEM tool.